Frequency of mycological diagnosis in a clinical laboratory in the city of Pelotas, south of Brazil, during the three-year period (2020-2023) - C. S. Svenson; F. R. P. Bruhn; C. E.S. Becker; M. C. Jara; P. S. Nascente (Brazilian Journal of Biology)
Abstract The increasing prevalence of immunosuppressive diseases, the increase in the elderly population, and globalization have led to the urgent need for research on the epidemiology and prevalence of fungi that cause mycoses in Brazil and worldwide. This is especially important, in the case of Brazil, for the South region, which currently lacks updated data on the subject. To this end, the objective was to investigate fungi diagnosed in mycoses by a laboratory in the city of Pelotas, South of Brazil. An observational and analytical survey was conducted for three years to analyze fungal diagnoses in the laboratory. Statistical analyses were performed by using SPPS and Joinpoint software. In total, 1220 fungal diagnoses were conducted, with 169 (13,8%) in 2020, 399 (32,7%) in 2021, 470 (38,5%) in 2022, and 182 (15,0%) in 2023, showing an increase in diagnoses over the years, with women seeking more diagnoses than men. Spring and summer were the seasons with the most diagnoses, and cutaneous and opportunistic mycoses were the most prevalent. Dermatophytes were the most diagnosed, followed by Candida spp. However, there was an increase in non-dermatophyte fungi diagnosed for onychomycosis. Therefore, despite the increase in the number of diagnoses over the years, it is important and necessary to establish standards for diagnosis in Brazil and worldwide for fungal diseases, especially the mandatory notification of serious mycoses. This will raise awareness in the healthcare sector and the public about the importance of diagnosing and treating fungal infections, which cause many fatalities every day.